Electrochemical determination of dinitolmide in poultry product samples using a highly sensitive Mn2O3/MCNTs-NPs carbon paste electrode aided by greenness assessment tools. (15th July 2022) - Kelani, Khadiga M.; Abdel-Raoof, Ahmed M.; Ashmawy, Ashraf M.; Omran, Gamal A.; Morshedy, Samir; Wafaa Nassar, Ahmed M.; Talaat, Wael; Elgazzar, Elsayed
Highlights: Optimization of a carbon paste voltammetric sensor for dinitolmide assay. The green chemistry proposed method was assessed by Analytical Eco-Scale and GAPI approaches. Fast direct determination of Dinitolmide without sample preparation or derivatization. The analytical method was validated according to the international conference on Harmonization (ICH). Abstract: In this paper, chemically modified carbon paste Mn2 O3 /MCNTs-NPs electrode for estimation of dinitolmide (DOM) utilizing square wave voltammetry method (SWV) was developed. The study investigated the electrochemical behavior of DOM, and the morphology of the modified electrode was evaluated by Scanning Electron Microscope (SEM) and Transmission Electron Microscope (TEM). The voltammetric behavior of DOM at modified electrode was recorded at a scan rate of 100 mVs −1 against Ag/AgCl reference electrode in phosphate buffer pH 4.0 within linearity range 2–12 µM, LOQ, and LOD of 1.8 and 0.594 µM, respectively, with average % recovery of (100.89 ± 0.795). GAPI and Analytical Eco-Scale tools were applied for greenness assessment. Specificity and interference study was valid for the proposed method; allowing DOM to be determined in its acidic degradation and its major interference drug. The proposed method was successfully employed to quantify DOM in bulk powder, egg, and frozen cuts-up chicken muscle samples.